The genus Hydrometra Latreille in Ecuador with description of a new species (Hemiptera: Heteroptera: Gerromorpha: Hydrometridae) - Cianferoni, Fabio; Buzzetti, Filippo Maria (Zootaxa, 2012)
Hydrometra argentina Berg is reported for Ecuador for the first time. H. aequatoriana n. sp. is described from westernAndean Ecuador. Male terminalia separate this species from other congeneric species. Four species of Hydrometra arenow known to occur in Ecuador: H. argentina, Hydrometra caraiba Guérin-Méneville, Hydrometra williamsi Hungerford & Evans and H. aequatoriana n. sp.